Leaf area profile of two sunflower cultivars under different rates and timing of nitrogen application - Mundstock, Claudio Mario; Zagonel, Jeferson (Pesquisa Agropecuaria Brasileira, 1994)
Nitrogen applied at different rates or timing affects the canopy leaf area and leaf expansion varies according to its position through the profile. N application in a field experiment with two sunflower hybrids affected the leaf area at different positions of the plant: leaves at the middle of the canopy expanded more as more nitrogen was available. The bottom leaves changed little in size, either by different N rates or timing. Early nitrogen applications, as well as higher N rates, resulted in more leaf expansion in the central part of the canopy, with decreasing effects as application is delayed or N decreased. The hybrid DK 180 had more total leaf number and more leaves in the central-upper part of the canopy, which responded more effectively to the treatments applied.
Keywords: Helianthus annuus; canopy; foliage; nitrogen